Deiksis Bahasa Jepang dalam Studi Linguistik Pragmatik - Akhmad Saifudin (Universitas Dian Nuswantoro, 2019)
Â This paper examines the use of deixis in Japanese. Deixis is one of the language phenomena whose frequency of occurrence in speech activities is many and varied. Basically, there are three types of deixis, namely person, spatial, and time. There are now two additional deixis, social deixis and discourse. This paper attempts to recognize the characteristics of Japanese deixis. With the aim that the data obtained is more varied, the data of this paper does not come from one source, but from various sources on the internet. By using the Pragmatic approach and theories about deixis (Fillmore, 1975; Hasegawa, 2012; Kuno & Kaburaki, 1977; Levinson, 1983; Lyons, 1977; Wetzel, 1988), this paper concludes that social and psychological contexts play a significant role very important in the use of Japanese language deixis. Social deixis and emphatic are central in Japanese deixis studies.